The Influence of Organizational Culture on Organizational Citizenship Behavior (OCB) With Job Satisfaction as An Intervening Variable at The Indonesian Quarantine Agency - Sugiono, Edi; Nurhasan, Acang (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study aims to analyze the influence of Organizational Culture on Organizational Citizenship Behavior (OCB) with Job Satisfaction as an intervening variable at the Indonesian Quarantine Agency. Human Resource Management plays a crucial role in organizational effectiveness, one of which is through the application of OCB that can improve overall organizational productivity. OCB is a voluntary behavior exhibited by employees to assist in organizational productivity without any formal obligation. This research uses an explanatory research method with a quantitative approach. Data were collected through questionnaires distributed to 108 employees of the Indonesian Quarantine Agency and analyzed using SmartPLS 3 software. The findings show that Organizational Culture has a positive and significant effect on OCB. A strong organizational culture encourages employees to collaborate, create a stable work environment, and develop skills and experiences that contribute to OCB behavior. Furthermore, Organizational Culture also significantly affects Job Satisfaction. An innovative, stable, and collaborative work environment motivates employees to feel more satisfied with their work, which in turn enhances their work motivation. Another finding in this study is that Job Satisfaction acts as an intervening variable that strengthens the relationship between Organizational Culture and OCB. With these findings, it is expected that the Indonesian Quarantine Agency will pay more attention to the implementation of Organizational Culture that supports employee job satisfaction. The organization can strengthen its work culture by increasing employee involvement in decision-making processes, providing career development opportunities, and creating a work environment that supports collaboration and innovation. Thus, it is hoped that a positive organizational culture will continue to be maintained to enhance team effectiveness and overall organizational productivity.